Factors Influencing Smoking Behavior in High School Students - Iswandi; Rahmadi (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2025)
Smoking behavior among senior high school students remains a significant public health and educational concern. This study aims to identify and analyze the factors that influence smoking behavior among senior high school students. The research employs a qualitative descriptive approach, with data collected through observations, interviews, and documentation. The findings indicate that several factors contribute to students’ smoking behavior, including peer influence, family environment, curiosity, and exposure to social and mass media. Peer pressure emerges as the most dominant factor, as students tend to imitate the behavior of their social groups to gain acceptance. Additionally, lack of parental supervision and insufficient awareness of the health risks associated with smoking further reinforce this behavior. The study concludes that comprehensive collaboration between schools, families, and communities is essential in preventing and reducing smoking behavior among students.